2003
DOI: 10.1161/01.cir.0000066322.21016.4a
|View full text |Cite
|
Sign up to set email alerts
|

Improved Exercise Tolerance and Quality of Life With Cardiac Rehabilitation of Older Patients After Myocardial Infarction

Abstract: Background-Whether cardiac rehabilitation (CR) is effective in patients older than 75 years, who have been excluded from most trials, remains unclear. We enrolled patients 46 to 86 years old in a randomized trial and assessed the effects of 2 months of post-myocardial infarction (MI) CR on total work capacity (TWC, in kilograms per meter) and health-related quality of life (HRQL). Methods and Results-Of 773 screened patients, 270 without cardiac failure, dementia, disability, or contraindications to exercise w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
142
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(155 citation statements)
references
References 27 publications
(6 reference statements)
7
142
0
6
Order By: Relevance
“…Only 4 trials, 8,[18][19][20] describing 6 different interventions (8% of total sample), provided complete information about all 7 core items required for replication. Intervention setting (Item 7) was consistently well reported across the original studies and assessed as complete in 89% of interventions.…”
Section: Description Of Cardiac Rehabilitation Interventions In Origimentioning
confidence: 99%
See 1 more Smart Citation
“…Only 4 trials, 8,[18][19][20] describing 6 different interventions (8% of total sample), provided complete information about all 7 core items required for replication. Intervention setting (Item 7) was consistently well reported across the original studies and assessed as complete in 89% of interventions.…”
Section: Description Of Cardiac Rehabilitation Interventions In Origimentioning
confidence: 99%
“…Only 19 interventions (26%), across 6 publications, 8,17,19,21,22 reported on planned strategies to enhance intervention fidelity and how this was assessed (Item 11). No mention of intervention modification (Item 10), from the original protocol or during the trial process, was made in any original publication.…”
Section: Description Of Cardiac Rehabilitation Interventions In Origimentioning
confidence: 99%
“…It has been suggested that interventions to reduce psychological distress have the potential to improve long-term cardiac prognosis [11]. Cardiac rehabilitation has been shown to improve depression [12], anxiety [13], and quality of life among patients with CHD [14]; however, as many as 50% of patients undergoing cardiac rehabilitation following myocardial infarction (MI) suffer from clinically high levels of psychological distress [15]. A combined treatment package of outpatient counselling, cardiac rehabilitation and cognitive behavioural therapy has been shown to improve psychological morbidity and quality of life among refractory angina patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…Unabhängig von den jeweiligen Komorbiditäten profitieren ältere Menschen von einem individuell angepassten körperlichen Training in gleicher Weise wie jüngere -nur ausgehend von einer niedrigeren Ausgangsbelastbarkeit [168,180,191,192,269,410,411,[424][425][426][427][428][429][430][431][432][433][434]. Im Rahmen eines Ausdauertrainings von 3 Monaten konnte bei älteren Menschen eine Verbesserung der Leistungsfähigkeit von 34-53% gezeigt werden [410,435].…”
Section: äLtere Menschenunclassified